2014
DOI: 10.1111/1750-3841.12404
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Antioxidant Capacities of 10 Common Edible Flowers from China

Abstract: The free and bound phenolic compounds in 10 common Chinese edible flowers were investigated using reversed phase high-performance liquid chromatography. Their antioxidant capacities were evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activity, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical-scavenging activity, oxygen radical absorption capacity (ORAC), ferric reducing antioxidant power (FRAP), and cellular antioxidant activity (CAA). Free factions were more prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
74
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 42 publications
15
74
3
1
Order By: Relevance
“…Oxygen radical absorbance capacity of OF fl owers was shown in Table 2. Literature provides no data for ORAC of OF, but the obtained value -333.23 μmol Trolox/g fl owers (dry weight) -was comparable to results noted for some edible fl owers used as herbs or food ingredients [Xiong et al, 2014].…”
Section: Antioxidant Properties Of Eof In Vitrosupporting
confidence: 70%
“…Oxygen radical absorbance capacity of OF fl owers was shown in Table 2. Literature provides no data for ORAC of OF, but the obtained value -333.23 μmol Trolox/g fl owers (dry weight) -was comparable to results noted for some edible fl owers used as herbs or food ingredients [Xiong et al, 2014].…”
Section: Antioxidant Properties Of Eof In Vitrosupporting
confidence: 70%
“…Phenolic agents present in plants have strong in vitro and in vivo antioxidant activities associated with their ability to scavenge free radicals, break free-radical chain reactions, and chelate metals. Increased consumption of phenolic agents has been correlated with antiinflammatory activity and a reduced risk of cardiovascular disease and certain cancers [23]. We discovered that the antioxidant activity of the ethanol extract of RMF and the fractions from the extract were closely correlated with their total phenolic content or total flavonoid content.…”
Section: Discussionmentioning
confidence: 89%
“…There is no such report for Petasites japonicus; as far as we know, Rosa species contain polyphenolic compounds with antioxidant activities [12]. We examined the effects of the extracts on HIV-1 replication in human cells.…”
Section: Rt Inhibition By Extracts Of Edible Flowersmentioning
confidence: 99%
“…In the present study, we tested the inhibitory activities of 43 edible plants towards DNA polymerase and RNase H activities of HIV-1 RT. Edible flowers are now receiving much interest from researchers due to the various effects they can exert, such as antioxidant and antidiabetic effects [11,12]. The results of this study revealed that ethanol and water extracts of Brasenia schreberi and water extract of Petasites japonicus strongly inhibit the activities of both DNA polymerase and RNase H. We also showed that these extracts strongly inhibit HIV-1 replication in human cells, suggesting that this may involve the inhibition of both the DNA polymerase and RNase H activities of HIV-1 RT.…”
Section: Introductionmentioning
confidence: 99%